287Human induced pluripotent stem cells for tissue-engineered cardiac repair. (15th July 2014) - Breckwoldt, K; Weinberger, F; Pecha, S; Geertz, B; Starbatty, J; Hansen, A; Eschenhagen, T
Abstract: Myocardial infarction causes unrecoverable loss of cardiomyocytes. Engineered heart tissue (EHT) is an in vitro model of three-dimensional, force generating cardiomyocyte network with morphological and functional similarity to native heart tissue. In this study we transplanted EHTs from human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes (CM) on cryo-injured guinea pig hearts and investigated whether hiPSC-CM-EHTs support left ventricular function. Human iPSC were generated by retroviral reprogramming of dermal fibroblasts. Cardiac differentiation of hiPSC was performed by an embryoid body-based three-stage differentiation protocol. EHTs were created from hiPS-CM (5*10^6 cardiomyocytes and 2*10^6 GFP+-HUVECs per EHT) and cultivated for 3 weeks under auxotonic stretch between flexible silicone posts. Development of contractile force was monitored prior to transplantation. Left ventricular myocardial cryo-injury was induced in adult guinea pigs (n=21). 7 days after injury EHTs (2 per animal, n=12) or cell-free constructs (n=9) were implanted. Animals received ciclosporin and methylprednisolon for immunosuppression. Functional parameters were examined by echocardiography and histology at baseline, before and 28 days after transplantation. The cardiac differentiation protocol resulted in a cell population with 50% cardiomyocytes, which was further enriched by lactate-based selection to >90% purity and directly used for EHT generation. HiPSC-CM-EHTs developed contractile force and displayed morphological properties of native heart tissue. Cryo-injury resulted in large transmural scars ( 30% of ventricular wall) which were verified histologically. Immunohistochemical staining for dystrophin and MLC2v showed the formation of large islets of cross-striated muscle tissue in the scar. The human origin was demonstrated by fluorescent-in-situ-hybridization. The new myocardium was vascularized with endothelium partly being of human origin. Animals receiving cell-free constructs showed left ventricular dilatation 28 days after transplantation. The EHT-group showed less dilatation (8.12 mm ± 0.21 basal, 8.18 mm ± 0.23 7d post cryo-injury, 8.87 mm ± 0.41 28d EHT vs. 9.74 mm ± 0.72 28d control) and significantly better fractional area shortening (42.20% ± 1.92 basal, 26.07% ± 2.13 7d post cryo-injury, 41.98% ± 4.48 28d EHT vs. 23.00% ± 3.24 28d control). Transplantation of hiPSC-derived EHTs in a guinea pig cryo-injury model provides early evidence that human EHTs survive after transplantation and support cardiac function.